2016
DOI: 10.1517/14656566.2016.1146683
|View full text |Cite
|
Sign up to set email alerts
|

Review on the clinical use of eribulin mesylate for the treatment of breast cancer

Abstract: Eribulin mesylate is a novel microtubule dynamics inhibitor compound important for the management of MBC and can be used for the treatment of patients who have previously received one/two chemotherapeutic regimens for metastatic disease and whose prior therapy included an anthracycline and a taxane. It's toxicity profile is acceptable and presents several favorable features namely a low probability of drug-drug interactions in the clinical setting, easy administration as bolus, low hypersensitivity chances and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…In this context, there is a keen interest to develop therapeutic alternatives with high cytotoxicity against MDR cancer cells. The recent FDA-approval of eribulin mesylate that overcome the MDR cell phenotype 41 , 42 illustrates this effort. In our study, PP-13 was shown to overcome efflux-mediated chemoresistance and could thus present a strong advantage over vinca-alkaloids that are actively effluxed by MRP1 and P-glycoprotein transporters or over taxanes that are exported by P-glycoprotein and MRP2 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is a keen interest to develop therapeutic alternatives with high cytotoxicity against MDR cancer cells. The recent FDA-approval of eribulin mesylate that overcome the MDR cell phenotype 41 , 42 illustrates this effort. In our study, PP-13 was shown to overcome efflux-mediated chemoresistance and could thus present a strong advantage over vinca-alkaloids that are actively effluxed by MRP1 and P-glycoprotein transporters or over taxanes that are exported by P-glycoprotein and MRP2 16 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Eribulin mesylate (EM, Halaven ® , E7389), a synthetic analog of the marine natural product halichondrin B, isolated from the Japanese marine sponge Halichondria okadai, is a nontaxane microtubule dynamics inhibitor, with a different site and mechanism of action as compared to taxanes and vinca-alcaloïds. 4 EM was approved by the US Food and Drug Administration (FDA) on November 15, 2010, and by the French regulatory authorities on March 22, 2012, based on the results of the pivotal open-label phase III randomized study EMBRACE. 5 The study compared EM monotherapy vs. treatment of physician's choice (TPC) in MBC patients previously treated with anthracyclines, taxanes and, for most patients, capecitabine.…”
Section: Introductionmentioning
confidence: 99%
“…Eribulin mesylate is a synthetic analogue of halichondrin B that inhibits the dynamics of the microtubules in the cell leading to cell‐cycle arrest and apoptosis . Eribulin is active, with manageable safety profile in metastatic breast cancer patients previously treated with taxanes and anthracyclines .…”
Section: Introductionmentioning
confidence: 99%